Experiências de internacionalização da educação superior de/em casa no contexto de uma rede de pesquisa latino-americana - Mazzetti, Antônio Carlos (2023)
This thesis is part of the Higher Education (HE) field of research and focuses on internationalization. This research takes place in the context of the Graduate Program in Regional Development (PPGDR), in the Line of Education and Development Research, of the Federal University of Technology - Paraná (UTFPR). The main point of this research is to analyze, from the perspectives of other Latin American regionalities, experiences of internationalization from/at home as decolonizers in/of research networks. To this end, I sought to identify and analyze decolonizing experiences of internationalization of higher education from/at home in a Latin American research network, with the objectives of: problematize Latin America as an epistemic and pluriverse place; analyze a Latin American research network as a place of interaction, in the process of detachment from the modern/colonial model. The theoretical-methodological assumptions are based on the decolonial and epistemological perspective from the South, in order to enable the decolonial turn that I printed in the look and sensitivity towards/with the subjects and place of research. In a scenario where the production of contemporary knowledge places us in contradictory and non-linear movements and challenges us to reflect on and beyond higher education, I position myself as a researcher from the South and to the South, from my place as an academic, contributing to the construction of knowledge, from the perspectives of other Latin American regionalities. I start from the assumption that Latin America and the Caribbean (LAC) is an epistemic place and is made up of pluriversal experiences, where the internationalization of higher education is inserted in this complex scenario of global and regional movements. On the other hand, internationalization of higher education from/at home has gained space in debates, although there is still a need to broaden discussions about real possibilities and intentions in Latin America. The heterogeneity of LAC brings the possibility of a logical inversion on the way that this issue is approached, transcending the modern/colonial model of higher education in Latin America and sensitizing us with diverse knowledge from the global South, searching for possibilities through detachment and peripheral knowledge. In this context, collaborative networks involving people and regional subjects are inserted, such as RIES, my research place, composed of researchers who, inserted in their place of study and enunciation, seek in the internal and external interaction other possibilities to produce and disseminate knowledge locally. This thesis analyzed and examined trends in the detachment of modern/colonial structures in RIES, as a Latin American research network, focusing on lived and shared experiences of the Network in the field of knowledge and, more specifically, regarding the internationalization of higher education from/at Home. In this context, it was possible to verify that, from the perspectives of other Latin American regionalities, the internationalization from/at home is a decolonizing experience of/in the networks.